Effects of landscape configuration and composition on phylogenetic diversity of trees in a highly fragmented tropical forest. (17th October 2016) - Matos, Fabio Antonio R.; Magnago, Luiz Fernando S.; Gastauer, Markus; Carreiras, João M. B.; Simonelli, Marcelo; Meira‐Neto, João Augusto A.; Edwards, David P.
Summary: Fragmentation of tropical forests is a major driver of the global extinction crisis. A key question is understanding how fragmentation impacts phylogenetic diversity, which summarizes the total evolutionary history shared across species within a community. Conserving phylogenetic diversity decreases the potential of losing unique ecological and phenotypic traits and plays important roles in maintaining ecosystem function and stability. Our study was conducted in landscapes within the highly fragmented Brazilian Atlantic forest. We sampled living trees with d.b.h. ≥ 4.8 cm in 0.1 ha plots within 28 fragment interiors and 12 fragment edges to evaluate the impacts of landscape configuration, composition and patch size, as well as edge effects, on phylogenetic diversity indices (PD, a measure of phylogenetic richness; MPD, phylogenetic distance between individuals in a community in deep evolutionary time; and MNTD, phylogenetic distance between each individual and its nearest phylogenetic neighbour). We found that PD and MPD were correlated with species richness, while MNTD was not. Best models suggest that MPD was positively related to edge density and negatively related to the number of forest patches, but that there was no effect of landscape configuration and composition metrics on PD or MNTD, or on standardized values of phylogenetic structure (sesPD, sesMPD and sesMNTD), which control for species richness. Considering all selected models for phylogenetic diversity and structure, edge density and number of forest patches were most frequently selected. With increasing patch size, we found lower PD in interiors but no change at edges and lower sesMNTD regardless of habitat type. Additionally, PD and sesMNTD were higher in interiors than at edges. Synthesis . Changes in MPD and sesMNTD suggest that extirpation of species at edges or in highly fragmented landscapes increases the dominance of species within a subset of clades (phylogenetic clustering), likely those adapted to disturbance. Smaller patch sizes are phylogenetically diverse and overdispersed, probably due to an invasion of edge‐adapted species. Conservation must enhance patch area and connectivity via forest restoration; pivotally, even small forest patches are important reservoirs of phylogenetic diversity in the highly threatened Brazilian Atlantic forest. Abstract : Changes in mean pairwise distance (MPD) and standardized mean nearest taxon distance (sesMNTD) suggest that extirpation of species at edges or in highly fragmented landscapes increases the dominance of species within a subset of clades (phylogenetic clustering), likely those adapted to disturbance. Smaller patch sizes are phylogenetically diverse and overdispersed, probably due to an invasion of edge‐adapted species. Conservation must enhance patch area and connectivity via forest restoration; pivotally, even small forest patches are important reservoirs of phylogenetic diversity in the highly threatened Brazilian Atlantic forest.